The Role of the Education Quality Assurance Agency (LPMP) in the Education Quality Assurance System (Multi Site Study at 3 Assisted Junior High Schools in Manado City) - Panungkelan, Florens S.T.; Senduk, J.F; Tuerah, Philoteus E A; Rawis, J A M (Universitas Malikussaleh, 2020)
This study focuses on the role of the North Sulawesi Education Quality Assurance Agency (LPMP) in the education quality assurance system in 3 junior high schools (SMP) assisted in Manado City. This research includes quality mapping which refers to quality report cards, supervision activities, and facilitation activities carried out at the target schools that are the research locations. The problem of this research is formulated as follows: What is the role of the Education Quality Assurance Agency (LPMP) in mapping the quality of education in 3 assisted junior high schools in Manado City? 3) What is the role of the Education Quality Assurance Agency (LPMP) in facilitating education at 3 target SMP in Manado City?. This study uses a qualitative approach with descriptive analytic methods designed by a multi-site study design. Data collected through observation and documentation. Analysis of the data used includes the flow of activities that occur simultaneously, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that: 1) The role of North Sulawesi LPMP in quality mapping in the target schools of Manado City is carried out with training and guidance as well as workshops at the target schools. Dissemination of filling in quality report cards and making quality report cards a reference in the preparation of school activity plans and budgets (RKAS). The 3 schools assisted by LPMP in North Sulawesi paid attention by inviting the target schools for each activity; 2) Quality supervision carried out by North Sulawesi LPMP at the target schools can be seen from the stages that are passed such as problem identification, recommendations, implementation assistance, monitoring and evaluation, and quality changes. During the Covid 19 pandemic, the implementation of quality supervision was carried out by utilizing information technology that could minimize the transmission of Covid 19. 3) The role of facilitation and assistance of LPMP in North Sulawesi was carried out by implementing the strategy for implementing the facilitation and mentoring activities of the target schools with three stages: preparation of the target school work program. SPMI, then the implementation and assistance of SPMI target schools, as well as dissemination activities.